Study of the Optical Properties of Optical Fibers - Ali, Mais Imad; Ahlaam Jasim Khlywi; Hussein, Zahraa kareem; Ghasim, Murtdha Kareem (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
These systems were operated at the wavelength of 1550 nm, where the loss is less than at the wavelength of 1300 nm. The development of the elements used in these systems, such as sources and detectors, led to the construction of systems that operate at an information transfer rate of Sec/GB10 (research continued to develop the elements of communications systems). Optical fibers to obtain the best operating conditions, which paved the way for the emergence of the fifth generation, which provided numerical elements. This was the beginInnsteinadg of the improvement of the sensitivity of the receiving devices, as heterodyne detection (from detection) was used. Direct, which enables efficient means of channel selection in systems that use Wavelength Division Mull-(WDM)tiplexing. Researchers were able to graft glass fibers with erbium (this grafting led to high-gain pumps called eribum doped fiber amplifiers (s, EDFA). In transportation lines and did not Amplifiers fiber Doped Erbium (which have found widespread use, The use of erbium-doped fibers is limited only to pumps, but extends to the use of lasers, switches, and many nonlinear devices. S,EDFAS amplifiers have also paved the way for fast communication systems and the emergence of transmission systems based on the use of natural pulses (solitons). Which enables it to cover long distances without deformation. These rapid developments have led to the widespread use of fiber optic communications systems throughout the world Used even for long-distance communications, whether onland or on land, Starting from the fields of communications, Or across the, Fibers Optical, An optical fiber is a guide wave (and is usually made of an electrical insulating material, or the optical fiber consists of two concentric cylinders. The central cylinder is called the core) and has an optical density (refractive index) symbolized by (1n ) which is higher than the optical density. For the outer cylinder (2n ) which is called the cladding (and this condition is (2n>1n ) It works to ensure that the transmission of light in the fiber is according to the principle of total internal reflection (Total). The two-layer fiber is covered with a thick plastic jacket to protect it from external influences. Optical fibers are usually made of tempered glass